2020
DOI: 10.1002/cft2.20030
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction problems and subsoiling effects on potato crops: A review

Abstract: Subsoil compaction is universally known to have negative impacts on crop production. These impacts are prominent in modern mechanized systems that rely on extensive use of heavy field machinery. Potato (Solanum tuberosum L.) is an intensively managed crop with yields often limited by subsoil compaction and tillage pans. The mechanical loosening of compacted soil via subsoiling is often believed to be a useful method to enhance root elongation and improve a crop's ability to access deeper soil water. This is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Despite the higher soil water content in trial 2 ( Figure 5 ), root density did not significantly differ between trials ( Table 3 ). Higher soil water content in compacted soil ( Figure 5 ) could reduce aeration ( Ghosh and Daigh, 2020 ) and soil oxygen availability and thus root growth ( Nguyen et al., 2020 ). As soil compaction decreased Inca Bella root density similarly in both trials ( Figure 9 ), despite higher soil water content in trial 2, it is unlikely that poor soil aeration is responsible for the lower root density in compacted soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the higher soil water content in trial 2 ( Figure 5 ), root density did not significantly differ between trials ( Table 3 ). Higher soil water content in compacted soil ( Figure 5 ) could reduce aeration ( Ghosh and Daigh, 2020 ) and soil oxygen availability and thus root growth ( Nguyen et al., 2020 ). As soil compaction decreased Inca Bella root density similarly in both trials ( Figure 9 ), despite higher soil water content in trial 2, it is unlikely that poor soil aeration is responsible for the lower root density in compacted soil.…”
Section: Discussionmentioning
confidence: 99%
“…Potato fields worldwide often have levels of soil compaction that limit root growth ( Stalham et al., 2007 ; Johansen et al., 2015a ; Sinton et al., 2022 ). Often, these fields are kept well-irrigated throughout the growing season to avoid soil water deficit and infections from diseases such as common scab ( Johansen et al., 2015b ), but wet soils are more susceptible to compaction than dry soils ( Ghosh and Daigh, 2020 ). Furthermore, if there is high crop water uptake from the topsoil, but high-volume irrigation events that infiltrate into deeper soil ( Reyes-Cabrera et al., 2016 ), the interface of wet and dry soil layers can be especially sensitive to compaction ( Batey, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional plowing, Pierce and Burpee (1995) found that no-tillage in the spring increased marketable yields, but not overall yields. Ghosh and Daigh (2020) concluded that potato yield and quality improvements from subsoiling are rare, temporary, and highly variable, with the only exception being when moisture is known to be the major limiting factor in a field. A similar trend was observed in the potato straw.…”
Section: Discussionmentioning
confidence: 99%
“…The root dry matter increased by 7.765% at the first location and 7.830% at the second location for the subsoiled plots over that of nonsubsoiled soil. The negative impacts of subsoil compaction could be alleviated by subsoil tillage, which can be an effective practice to reduce bulk density (Table 4), and provide more space between soil particles, therewith, facilitating root penetration into compacted subsoil that might facilitate root absorption of water and nutrients in deep subsoil [35].…”
Section: Root Dry Mattermentioning
confidence: 99%